Developing immunotherapy strategies in the treatment of prostate cancer - James L. Gulley; Ravi A. Madan (Asian Journal of Urology)
The clinical development of immunotherapy has gained significant impetus in recent years across the field of medical oncology. Mounting preclinical and clinical data have demonstrated the potential of immune-based treatments to augment anti-tumor immune responses. With one of the first modern immunotherapies approved in prostate cancer and multiple others in late stage development, immune treatment strategies need to be optimized to ensure the best clinical outcomes. Combination strategies with androgen deprivation therapy, anti-androgen therapy, radiation and chemotherapy have demonstrated the potential maximize immune response in prostate cancer patients. These combinations are currently being evaluated in clinical trials at every stage of prostate cancer from the newly diagnosed to the most advanced stages. Data from these studies will provide guidance for the future clinical implementation of immunotherapy in prostate cancer. Keywords: Prostate cancer, Immunotherapy, Combination therapies